Surviving Amid the Pandemic: The Roles of Social Supports in Coping with Academic Stress among Thesis-Writing Students during the Pandemic - Andrias Cahya Purnama; Fitriana Widyastuti (Psikostudia : Jurnal Psikologi, 2026)
The shift from face-to-face to remote learning due to the COVID-19 Pandemic has triggered academic stress in students, including those completing their thesis writing. The research aims to investigate the role of social support in alleviating the academic stress of students completing their thesis during the COVID-19 pandemic. It involved 100 respondents (40 males and 60 females), who were selected using quota sampling techniques. The research employed a correlational quantitative design. Academic stress was measured using an Academic Stress Scale, while social support was measured using a Social Support Scale. Furthermore, regression analysis was employed to investigate the relationship between social support and academic stress. The findings showed a negative correlation between social support and stress (F = 97.9, p < .001). Meanwhile, social support made an effective contribution by 50% (R2=0.500). The research also found that family and information support become stronger predictors of academic stress. Additionally, male and female students share similar potential to experience academic stress. The implications of these findings highlight the need to strengthen social support, particularly from family and through access to adequate information, in order to reduce academic stress among students working on their theses. Higher education institutions are also encouraged to develop academic mentoring programs and counseling services that focus on enhancing social support from academic advisors, peers, and the broader campus support system.Perubahan pembelajaran dari tatap muka menjadi pembelajaran jarak jauh akibat pandemic Covid-19 memicu stres akademik pada mahasiswa, termasuk pada mahasiswa yang sedang mengerjakan skripsi. Penelitian ini bertujuan untuk mengetahui peran dukungan sosial terhadap stres akademik pada mahasiswa yang sedang mengerjakan skripsi selama pandemic Covid-19. Penelitian ini melibatkan 100 responden (40 laki-laki dan 60 perempuan) yang diambil melalui teknik quota sampling. Penelitian menggunakan desain kuantitatif korelasional. Stres akademik diukur menggunakan Skala Stres Akademik sementara persepsi dukungan sosial diukur menggunakan Skala Dukungan Sosial. Peneliti menggunakan analisis regresi untuk menguji korelasi antara dukungan sosial dan stres akademik. Hasil penelitian ini menunjukkan bahwa terdapat hubungan negatif antara dukungan sosial dengan stres (F = 97.9, , p < .001). Dukungan sosial memberikan sumbangan efektif sebesar 50% (R 2 =0.500). Penelitian ini juga menemukan bahwa dukungan sosial keluarga dan dukungan informasi menjadi prediktor yang lebih kuat terhadap stres akademik. Penelitian ini juga menemukan bahwa laki-laki dan perempuan memiliki potensi yang sama mengalami stres akademik. Implikasi dari temuan ini menunjukkan bahwa perlunya penguatan dukungan sosial, khususnya dari keluarga dan akses terhadap informasi yang memadai untuk menurunkan stres akademik pada mahasiswa yang sedang mengerjakan skripsi. Perguruan tinggi juga disarankan untuk mengembangkan program pendampingan akademik dan layanan konseling yang berfokus pada peningkatan dukungan sosial dari dosen, teman sebaya dan sistem layanan kampus secara umum.